Matrix metalloproteinases are elevated in the urine of patients with endometriosis. - Becker, C; Louis, G; Exarhopoulos, A; Mechsner, S; Ebert, A; Zurakowski, D; Moses, M (2010)
In a prospective, blinded, longitudinal study MMP-2, MMP-9, and MMP-9/neutrophil gelatinase-associated lipocalin were significantly more likely to be detected in the urine of patients with endometriosis than in controls.